Human rights in mental healthcare; A review of current global situation. (17th February 2023) - Mahdanian, Artin A.; Laporta, Marc; Drew Bold, Nathalie; Funk, Michelle; Puras, Dainus
Abstract: The relationship between mental health and human rights is complex and bidirectional. Global mental health movements have been emphasizing the promotion of human rights in mental health care in accordance with the UN Convention on the Rights of Persons with Disabilities and the WHO QualityRights Initiative. The main objective of this review is to have an overview of the current global situation of human rights in mental health services by performing a review of scientific literature. The literature search and elimination process yielded a total of 26 articles focussing on human rights-related reports and tools. Further assessment of these articles clearly shows that despite significant improvements in mental health service delivery in the past decade, there is still substantial reporting of the continuing prominence of stigmatizing attitudes, and human rights violations and abuses in mental health settings. The human rights perspective requires society, particularly policymakers, to actively promote necessary conditions for all individuals to fully realize their rights. We suggest developing a more comprehensive model in mental health that integrates human rights into existing services and approaches. A model that recognizes that all people with mental health conditions and psychosocial disabilities are rights holders.